2016
DOI: 10.1093/nar/gkw1277
|View full text |Cite
|
Sign up to set email alerts
|

Binding site density enables paralog-specific activity of SLM2 and Sam68 proteins in Neurexin2 AS4 splicing control

Abstract: SLM2 and Sam68 are splicing regulator paralogs that usually overlap in function, yet only SLM2 and not Sam68 controls the Neurexin2 AS4 exon important for brain function. Herein we find that SLM2 and Sam68 similarly bind to Neurexin2 pre-mRNA, both within the mouse cortex and in vitro. Protein domain-swap experiments identify a region including the STAR domain that differentiates SLM2 and Sam68 activity in splicing target selection, and confirm that this is not established via the variant amino acids involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…They are characterized by a central KH-type RNA-binding domain and a C-terminal Sam68 domain, and function broadly in many events of alternative splicing in neuronal and non-neuronal cells (Chawla et al, 2009). Puzzlingly, all STAR-family proteins have been shown to be separately essential for neurexin alternative splicing at SS4 (Iijima et al, 2011 and 2014; Ehrmann et al, 2013; Traunmüller et al, 2016; Danilenko et al, 2017). Of these studies, the best evidence exists for SLM2.…”
Section: Neurexins: Form and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are characterized by a central KH-type RNA-binding domain and a C-terminal Sam68 domain, and function broadly in many events of alternative splicing in neuronal and non-neuronal cells (Chawla et al, 2009). Puzzlingly, all STAR-family proteins have been shown to be separately essential for neurexin alternative splicing at SS4 (Iijima et al, 2011 and 2014; Ehrmann et al, 2013; Traunmüller et al, 2016; Danilenko et al, 2017). Of these studies, the best evidence exists for SLM2.…”
Section: Neurexins: Form and Functionmentioning
confidence: 99%
“…In vitro experiments suggested that SLM2 and Sam68 can both enhance excision of SS4 in both Nrxn1 and Nrxn3 , but that only SLM2 and not Sam68 can do so in Nrxn2 because the Nrxn2 gene contains fewer binding sites for these factors (Danilenko et al, 2017). Additional mechanisms may contribute.…”
Section: Neurexins: Form and Functionmentioning
confidence: 99%
“…Previous work indicated that Sam68 is highly expressed in the motor neurons of the spinal cord ( Pagliarini et al, 2015 ), suggesting an important function of this protein in these cells. Sam68 is known to modulate splicing of several genes encoding for synaptic proteins ( Iijima et al, 2011 ; Danilenko et al, 2017 ; Witte et al, 2019 ; Farini et al, 2020 ). To test whether Sam68 regulates splicing of such synaptic genes in the spinal cord, we selected splicing events from several RNA-sequencing and microarray experiments carried out in Sam68-depleted mouse tissues or cells ( Ehrmann et al, 2008 ; Chawla et al, 2009 ; Iijima et al, 2011 ; Paronetto et al, 2011 ; La Rosa et al, 2016 ; Danilenko et al, 2017 ; Witte et al, 2019 ; Farini et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sam68 deficiency was also reported to impair motor coordination ( Lukong & Richard, 2008 ) and social behavior ( Farini et al, 2020 ). On the other hand, Sam68 has been involved in the pathogenesis of fragile X-associated tremor/ataxia syndrome ( Sellier et al, 2010 ) and spinal muscular atrophy ( Pedrotti et al, 2010 ; Pagliarini et al, 2015 ), as well as in brain development and function ( Iijima et al, 2011 ; Danilenko et al, 2017 ; Witte et al, 2019 ; Farini et al, 2020 ) through modulation of neuron-specific splicing events.…”
Section: Introductionmentioning
confidence: 99%
“…Much rather, it appears that the cellular context and/or signalling state have important impact on the alternative splicing regulation by these STAR proteins. Notably, previous work highlighted the possibility of differential activities based on heterodimer formation between STAR proteins and additional RNA‐binding proteins (RBPs) (Iijima et al., ) or the density of binding motifs in target mRNAs (Danilenko et al., ). This complexity highlights the challenges of predicting outcomes of alternative splicing regulation based on RBP expression or presence of binding motifs and emphasizes the necessity to interrogate alternative splicing programs using cell type‐specific methods in the future.…”
Section: Discussionmentioning
confidence: 99%